2011
DOI: 10.1111/j.1467-8543.2011.00851.x
|View full text |Cite
|
Sign up to set email alerts
|

International Framework Agreements and Industrial Relations Governance: Global Rhetoric versus Local Realities

Abstract: The article discusses the local impact of international framework agreements (IFAs). It presents findings from empirical research carried out in two Spanish MNCs, and it examines how the commitments stipulated by the texts of the IFAs translate in local practice in different subsidiaries in Central and SouthAmerica. The article follows the policy cycle of both agreements, and it further evaluates them as emerging private institutions of global industrial relations governance. The main findings reveal a paradox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 20 publications
0
105
0
6
Order By: Relevance
“…Meanwhile, most IFA research has been driven by an interest in transnational unionism and adopts a more pluralist perspective look at a broader set of factors that may explain whether IFAs will create space for new social dialogue, as well as a tool to forge coalitions with NGOs, other unions and social movements to organize workers around the globe (Telljohann et al, 2009;Papadakis, 2011;Niforou, 2012;Helfen and Fichter, 2013). These studies often combine different factors to explain the emergence or impact of the IFAs.…”
Section: The Internationalization Of Worker Representationmentioning
confidence: 99%
“…Meanwhile, most IFA research has been driven by an interest in transnational unionism and adopts a more pluralist perspective look at a broader set of factors that may explain whether IFAs will create space for new social dialogue, as well as a tool to forge coalitions with NGOs, other unions and social movements to organize workers around the globe (Telljohann et al, 2009;Papadakis, 2011;Niforou, 2012;Helfen and Fichter, 2013). These studies often combine different factors to explain the emergence or impact of the IFAs.…”
Section: The Internationalization Of Worker Representationmentioning
confidence: 99%
“…It has been argued that GUFs, as sectoral federations, are positioned in very different ways with regard to strategy and the implementation of action across production networks and this is also thought to shape the politics of inter-union relations (Cumbers et al, 2008). The need for GUFs to develop varied, carefully designed and contextappropriate strategies in order to exercise power and influence over employers and states has also been noted (Brookes, 2013: 194), while studies of specific campaigns and initiatives (Davies et al, 2011;McCallum, 2013;Niforou, 2012) have shown the significance of local or regional context in determining the success or failure of avowedly 'global' initiatives -whether it be the established organizational forms and repertoires of local or national unions or the configuration of politics, governance or employment relations in particular settings. This would appear to be especially relevant to the effect of global campaigns and regulatory initiatives on workplaces situated in the Global South where unions are often weak, fragmented and have limited institutional and associational power (Brookes, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…With regard to global agreement making, for instance, some studies have pointed to the positive effect of IFAs/GFAs under certain circumstances, but many others emphasize the limited translation of formal agreement making at global/corporate level into action by managers, workers and unions at industry or enterprise level (Davies et al, 2011;Niforou, 2012). This is in part a problem of the failure to build implementation measures into agreements that are ultimately far removed from local contexts.…”
Section: Agents Of Change or Marginal Actors?mentioning
confidence: 99%
See 1 more Smart Citation
“…Les moyens mis en oeuvre pour atteindre cet objectif consiste parfois à négocier la ratification d'un accord-cadre international (ACI), le plus souvent conclu entre la direction d'une entreprise multinationale et une fédération syndicale internationale (FSI). Sans se substituer aux législations nationales, ces accords formalisent un certain nombre d'engagements sociaux des entreprises en s'appuyant notamment sur les normes internationales minimales de travail de l'Organisation internationale du travail (OIT) (Fichter, Helfen et Sydow, 2011;Niforou, 2012;Papadakis, 2011).…”
unclassified